Living ruins of the Teatro de Arte Israelita Brasileiro (Brazilian Israelite Art Theatre) in the book TAIB: A history of theatre (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
Review of the book Taib: uma história do teatro (Taib: a history of theatre) about the trajectory of the theatre built by the Instituto Cultural Israelita Brasileiro (ICIB), maintained by the Jewish community of Yiddish culture in São Paulo in the 1960s. The analysis highlights how the book presents the unique character of that theatre, both for the Yiddish culture of the 1950s and 1960s and for Brazilian political theatre in the following decades. In the research carried out by the authors of the texts gathered in the book, it is also possible to see how the current ruins of the TAIB still bear the ghostly marks of a remarkable trajectory with the potential to be reactivated.
Keywords: TAIB; Yiddish theater; political theater; brazilian theater